Theorising Chinese urbanisation: A multi-layered perspective. (November 2015) - Gu, Chaolin; Kesteloot, Christian; Cook, Ian G
Urbanisation in China and its rapid increase in recent decades as a result of industrialisation and globalisation are often conceived as a simplified process. Moreover, the speed of the present day process yields the impression that the traces of previous forms of urbanisation are erased for good. Both of these assumptions are challenged in this paper. The built environment resulting from this urbanisation process is to be conceived as a series of layers that reflect different modes of productions and related logics of production of space. Hence, we try to comprehend the spatial arrangement of the city, which can be thought of as a geological metaphor. The social groups that have to be sheltered in urban residential space also radically change in each of these periods. We proceed to analyse these layers and how they combine and interact over time with the concept of socio-spatial configuration, which denotes a precise type of residential environment related to a specific social group in the city. Chinese cities are made up of five types of urbanisation, reflected in five layers and their related socio-spatial configurations: the traditional, proto-globalisation, socialist, market-led and globalisation layers.